The Effect Of Educational Misconduct On Ethical Decision-Making In A Professional Environment: An Investigation Of Engineering Students - Gaojie, Chen; Wenchuan, Wu (Migration Letters, 2024)
Background: The topic of academic misconduct has been investigated intensively across the world. When people embrace learning methodologies throughout their education, personal values are a field o[1]f study factor. These principles have a major impact on how people behave in their learning communities and, ultimately, how well they do academically, especially in college or university. This study aims to address the crucial issue of whether online assessment tools combined with a well-established teaching style via a Multi-Course Project-Based Learning (MPL) approach aid in achieving the successful completion of the SOs in a senior-level Electrical Engineering (EE) course. Aim: The aim of this research is to investigate the relationship between moral conduct in professional settings and integrity in academia. Method: This research investigated the link between moral decision-making and educational misconduct, with a concentration on the moderating role of ethical decision-making on this connection. It was conducted on the foundations of the social cognitive hypothesis and the theory of planned action. To verify the study’s assumptions, a survey of 1271 students—744 female and 527 male—with a mean age of 15.39 years and a standard deviation of 0.78—from 41 senior students studying engineering in China was completed and assessed using hierarchical regression techniques by SPSS 26. Results: The findings indicate that female students had less educational misconduct and a more favourable attitude towards making ethical decisions than did their male counterparts. Students who report engaging in dishonest behaviour outside of school also report perpetrating acts against their academic standing, while students who see academic infractions as less severe report engaging in academic misconduct more often outside of school. Conclusion: When developing courses on ethics or college student regulations that focus more on education misconduct and other pertinent topics, scholars from education and administrators in education systems may use the study’s results as a reliable source of knowledge.